Decentralization and Poverty in Indonesia: The Case of Karo District - Pandia, Sejahtera (JPAS (Journal of Public Administration Studies), 2016)
This study examines the link between decentralization and poverty. This study takes Karo District, an agricultural region, compared with Indonesia and North Sumatra Province. The result reveals that poverty rate is declining during 2002 to 2012 in Karo, North Sumatra Province and Indonesia. There is an opinion that with or without decentralization poverty tends to decrease because of industrialization accompanied by labor migration. North Sumatra and Indonesia as a whole support the opinion that industrialization may be a tool to overcome poverty, but it not the case for Karo. Industrialization has not been a â€œvehicleâ€ to poverty reduction in Karo since it has not undergone any industrialization. The equality of inter-regional fiscal capacity, the stepping-up of local peopleâ€™s participation and the improvement of local administrative apparatus seem to have had a positive impact on poverty reduction in Karo.